钛板对儿童下颌骨生长发育影响的长期随访研究 (Hua Xi Kou Qiang Yi Xue Za Zhi, 2015)
OBJECTIVE: To explore the impact of titanium implant on the growth and development of pediatric mandible after suffering from mandibular fracture and undergoing open reduction and internal fixation (ORIF) compared with those that underwent titanium plate removal postoperatively. METHODS: Fifteen pediatric patients with mandibular fracture who underwent ORIF were included in this study. Eight patients did not undergo titanium implant removal postoperatively, whereas the other seven patients underwent the routine. The postoperative data of the pediatrics were collected for comparative analysis by taking the patients' frontal and lateral photos, recording the inter-incisor distance, and measuring the height of mandibular ramus, length of the mandibular body, and combined length of the mandible in three-dimensional reconstruction image. RESULTS: All patients had acceptable facial contour, mouth opening, and occlusion, without obvious abnormalities. The radiography showed no significant difference between the bilateral mandibular lengths in the two groups of patients (P>0.05). CONCLUSION: The titanium plants have no significant impact on the growth and development of pediatric mandible postoperatively; hence, the question on whether the titanium plates should be removed or not may be neglected. The removal operation may lead to secondary trauma; thus, performing titanium plate removal routinely is not recommended.